2005
DOI: 10.1007/bf03016529
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged duration of anesthesia in a patient with multiple sclerosis following paravertebral block

Abstract: P Pu ur rp po os se e: : To explore the possibility that the prolonged duration of anesthesia following paravertebral block was related to the presence of multiple sclerosis in a patient undergoing elective inguinal hernia repair.C Cl li in ni ic ca al l f fe ea at tu ur re es s: : A healthy 33-yr-old female presented for elective inguinal hernia repair. The procedure was performed under general anesthesia and a paravertebral block was performed at the end of the procedure for postoperative pain relief, whilst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 10 publications
(6 reference statements)
0
13
0
5
Order By: Relevance
“…Use of higher current (> 1 mA) and a longer stimulation duration (> 0.3 msec) is recommended in these situations, but does not guarantee a successful block. 26 it has been suggested that local anesthetics may have an exaggerated effect on the spinal cord in the presence of demylination, 27 although this has not been confirmed in relation to peripheral nerve blocks. The patient described in case 1 had a chest wall deformity, and a good spread of local anesthetic around the axillary artery, was seen with a smaller volume requirement of local anesthetic.…”
Section: Discussionmentioning
confidence: 99%
“…Use of higher current (> 1 mA) and a longer stimulation duration (> 0.3 msec) is recommended in these situations, but does not guarantee a successful block. 26 it has been suggested that local anesthetics may have an exaggerated effect on the spinal cord in the presence of demylination, 27 although this has not been confirmed in relation to peripheral nerve blocks. The patient described in case 1 had a chest wall deformity, and a good spread of local anesthetic around the axillary artery, was seen with a smaller volume requirement of local anesthetic.…”
Section: Discussionmentioning
confidence: 99%
“…Even an increase of 0.5°C in body temperature is capable of reducing temporarily the neurological function 1,2 . General anesthesia 7,8 and anesthesia of the neuroaxis 7,11 have also been implicated as factors that can induce recurrences, although it is not widely accepted, being still a matter of controversy 1,4,6,12 . Perlas and Chan 4 stated that although the postoperative and postpartum recurrences are controversial, they are not affected by the choice of the anesthetic technique.…”
Section: Discussionmentioning
confidence: 99%
“…Tem sido referida como técnica mais inócua 7 , pois se sugere que a concentração de anestésico local na substância branca medular seja de 3 a 4 vezes menor do que na anestesia subaracnóidea 6,8,10,11 . A bupivacaína, a uma concentração maior do que 0,25%, causou exacerbação aguda pós-operatória em todas as pacientes que receberam anestesia peridural em um estudo realizado no Brigham and Women's Hospital no período entre 1982 e 1987 11 . A paciente obstétrica parece ser mais resistente à depressão respiratória tardia pós-operatória após o uso de opióides hidrofílicos no neuroeixo 15 .…”
unclassified
“…présentent un cas inhabituel de rachianesthésie accidentelle présumée à la suite d'un bloc paravertébral lombaire à deux niveaux chez une femme de 33 ans jugée en bonne santé au moment de l'intervention chirurgicale, mais chez qui on a diagnostiqué une SP par la suite. 13 Le bloc sensitif et moteur, bilatéralement étendu de T4 au sacrum, suivant l'administration de 60 mg de bupivacaïne a rendu les auteurs perplexes au sujet d'une possible administration intrathécale involontaire. La régression du bloc s'est prolongée ; il a régressé à T12, six heures et demie plus tard et a été complètement résolu de six heures et demie à onze heures après l'injection.…”
Section: Anesthésie Neuraxiale Etunclassified
“…10 Other case series did not describe the quality or duration of anesthesia. 11,12 In the current issue of the Canadian Journal of Anesthesia, Finucane et al report an unusual case of presumed unintentional spinal anesthetic following a two-level lumbar paravertebral block in a 33-yr-old lady who was deemed healthy at the time of surgery but was later found to have MS. 13 Extensive sensory and motor blockade from T4 to sacrum bilaterally following the administration of bupivacaine 60 mg, made the authors suspicious of unintentional intrathecal administration. Block regression was prolonged; the level regressed to T12 six and a half hours later, and completely resolved sometime between six and a half and 11 hr post-injection.…”
mentioning
confidence: 99%